TEACHING PHRASEOLOGISMS THROUGH INTERACTIVE METHODS - Bazarov Zokir Mekhriqulovich (Western European Studies, 2024)
In this article, it is noted about the study of the problems of teaching phraseological units in the English language and the forms of organization of modern lessons that are being developed in this regard. A system of exercises, a text translation method, and an interactive teaching method have been developed. Theories of language learning emphasize the need to learn phraseology as a part of vocabulary. Detailed information is given on how the essence of a phraseological unit, its components and its different interpretations depending on the understanding of the size of the phraseology are given
Keywords: Phraseological units; idiom; interactive method; linguistics